The use of a modified Suzuki reaction for the synthesis of monoarylferrocenes - Imrie, C; Loubser, C; Engelbrecht, P; McCleland, CW (Perkin transactions. 1, 1999)
A modification of the Suzuki cross-coupling reaction proved to be a clean and useful method for the preparation of monosubstituted arylferrocenes. Iodoferrocene was reacted with a series of substituted arylboronic acids in the presence of sodium carbonate and palladium acetate in aqueous ethanol at room temperature to produce a range of substituted monoarylferrocenes. A systematic investigation undertaken to determine optimal reaction conditions indicated that scrupulous deoxygenation of the solvent is critical. The use of stronger bases such as barium hydroxide and potassium carbonate is favourable and gives rise to better yields of monoarylferrocenes. The reactions also proceed efficiently in aqueous DMF, broadening the scope of the reaction allowing efficient reactions with boronic acids that show low solubility in organic solvents.